Application Of Connected Type Of Integrated Learning Model To Increase Learning Outcome Of XI Class Students In SMA Surya Buana - Rasyid, Muh. Anwar; Ugami Tr., Dwinisa Cahya; Balqis, Balqis (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
The implementation of learning for high school biology subjects in the Kurikulum Merdeka still often encounters obstacles. This study aims to analyze the application of the connected integrated learning model to improve learning outcomes. This research involved all 8 class XI Science students at SMA Surya Buana who were positioned as research subjects. Learning outcome data was collected using pre-test and post-test instruments. The results of this research show that there is an increase in the learning outcomes of class XI Science students by implementing the connected integrated learning model. Following up on the findings in this research, the connected integrated learning model is recommended with certain specific characteristics.